2023
DOI: 10.3390/ma16134868
|View full text |Cite
|
Sign up to set email alerts
|

Proposition of New Testing Procedure for the Mechanical Properties of Bulk-Fill Materials

Matea Macan,
Ana Marošević,
Bruno Špiljak
et al.

Abstract: This study analysed flexural properties, microhardness, and the degree of conversion (DC) of five bulk-fill composites under clinically relevant conditions (4 mm thick specimens) in comparison to 2 mm specimens according to ISO 4049. Additionally, the effect of rapid polymerisation on 4 mm specimens was evaluated after accelerated aging. DC was measured using Fourier transform infrared spectrometry at 2 and 4 mm thick layers, while flexural properties and Vickers microhardness were tested using 16 × 2 × 2 mm o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 39 publications
0
3
1
Order By: Relevance
“…On the other hand, Filtek as the sculptable material with the highest filler volume in this study, has previously also shown the highest flexural strength, followed by PowerFill and SDR+ (which were statistically similar), and PowerFlow [43]. However, in the present study, Filtek did not exhibit the highest bond strength in any of the curing protocols.…”
Section: Discussioncontrasting
confidence: 56%
See 3 more Smart Citations
“…On the other hand, Filtek as the sculptable material with the highest filler volume in this study, has previously also shown the highest flexural strength, followed by PowerFill and SDR+ (which were statistically similar), and PowerFlow [43]. However, in the present study, Filtek did not exhibit the highest bond strength in any of the curing protocols.…”
Section: Discussioncontrasting
confidence: 56%
“…However, in the present study, Filtek did not exhibit the highest bond strength in any of the curing protocols. This is probably due to its low DC value, as previously shown [42,43]. The distinctive feature of this material is a long, high-molecular-weight AUDMA molecule with only two methacrylate groups [44].…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations